Art and Politics between the Arab World and Latin America - Guirguis, Laure,; Pabón, Maru, (Islamicate and Ibero-American World Connections ;, 2025)
Intertwined with the histories of Arab migration to the Americas from the nineteenth century until now, the emergence of competing nationalist narratives within Arab communities in Latin America, and the birth of anti-imperialist and anticolonial struggles, the history of cultural entanglements between the Arab world and Latin America spans over a hundred years--and reveals the vital role of art in creating bridges between the two regions. This book, the first of its kind, gathers interventions that showcase the twentieth century as a period of intense redefinitions and cultural effervescence across the whole of Latin America and the Arab world. The result is a polished image of the twentieth century as a period whose shifting categories of affiliation were tied to events and movements that connected the two regions in ever deepening ways, and to forms of artful experimentation through which political ideologies, alternative collective identities, and aesthetic movements could be contested or embraced. Contributors are Diogo Bercito, Kevin Funk, Silvina Schammah Gesser, Laure Guirguis, Olivier Hadouchi, Julia Solana Jáuregui, John Tofik Karam, Edgardo Manero, Mariano Mestman, Gabriella Nugent, Maru Pabón, Laura Reali and Juan José Vagni.